Virtual Reconstruction-Based Robust Adaptive Beamforming for Distributed Digital Subarray Antennas - Jian Lu; Jian Yang; Bo Hou; Fengchao Zhu; Zhiyong Yu; Guangbin Liu (International Journal of Antennas and Propagation)
For the distributed digital subarray antennas (DDSA), the conventional beamforming may give rise to grating lobes, high sidelobes, and other problems. In this paper, the gaps between the subarrays are filled with virtual array elements, and then the DDSA can form a virtual contiguous array. More concretely, based on the direction-of-arrival (DOA) estimation of the signal sources, the interference components of the virtual elements and the interference-plus-noise covariance matrix (INCM) of the virtual contiguous array can be reconstructed. At low signal-to-noise ratio (SNR), the DOA estimation of the desired signal is implemented by subarray adaptive beamforming. Finally, with the steering vector of the desired signal and reconstructed INCM, the weight vector of the proposed beamformer can be obtained, which must be applied to the rearranged data matrix received by the actual and virtual elements. Simulation results are provided to demonstrate the effectiveness of the proposed algorithm.